The Development of Comic Learning Media in Primary Teacher Education’s Students of FKIP Untan - Maha Lastasabuju Basafpipana Habaridota (Universitas Tanjungpura, 2018)
This study aims to determine the development of learning comic media for students majoring in basic education FKIP UNTAN. The study was carried out in the department of basic education with 15 people. The data collected in the development of learning materials and the final product in the form of learning comics using data collection tools in the form of observation sheets (questionnaires) and documentation. Data analysis with several stages, namely: needs analysis, initial product creation, expert evaluation, first product revision, small group trial, product revision, field test, and final product. The results of the study show that comic feasibility can be shown by the assessment of material experts by 4.64 with the category of